Work Ethic and Organizational Culture Based On Performance of Employees at Takalar Sugar Factory PTPN XIV South Sulawesi - Nuraini Rasyid (Formosa Journal of Applied Sciences, 2024)
This research aims to: 1) Examine how work ethics affect employee performance; 2) Examine how organizational culture affects employee performance; and 3) Examine how work ethics and organizational culture interact to affect employee performance. Explanatory research using a quantitative research methodology is being conducted. Multiple regression analysis was the method of analysis employed in this investigation. The following are the study's findings: 1) Takalar Sugar Factory PTPN XIV South Sulawesi employees perform better when they have a strong work ethic. 2) Takalar Sugar Factory PTPN XIV South Sulawesi employees' work performance is positively and significantly impacted by their organizational culture, indicating that the better an employee's organizational culture, the better their job performance will